The answer to this question is b
Heya !
Given expression -
![3 {x}^{2} + 25 = 73](https://tex.z-dn.net/?f=3%20%7Bx%7D%5E%7B2%7D%20%2B%2025%20%3D%2073)
Subtracting 25 both sides ,
![3 {x}^{2} + 25 - 25 = 73 - 25 \\ \\ 3 {x}^{2} = 48](https://tex.z-dn.net/?f=3%20%7Bx%7D%5E%7B2%7D%20%2B%2025%20-%2025%20%3D%2073%20-%2025%20%5C%5C%20%5C%5C%203%20%7Bx%7D%5E%7B2%7D%20%3D%2048)
Dividing by 3 on both sides ,
![\frac{3 {x}^{2} }{3} = \frac{48}{3} \\ \\ {x}^{2} = 16](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%20%7Bx%7D%5E%7B2%7D%20%7D%7B3%7D%20%3D%20%5Cfrac%7B48%7D%7B3%7D%20%5C%5C%20%5C%5C%20%7Bx%7D%5E%7B2%7D%20%3D%2016)
Therefore ,
Answer:
1
Step-by-step explanation:
Anything to the power of 0 is 1. <em>So</em>,
1 x 1 = 1
Answer:
LEts start with 10^1
If we have positive exponent then we add zeros
10^1= 10
(Put 2 zeros because exponent is 2)
(Put 3 zeros because exponent is 3)
(Put 4 zeros because exponent is 4)
(Put 5 zeros because exponent is 5)
For negative exponent , we make a fraction . we put 1 at the top always and number as the bottom
(Put 1 zero at the bottom because exponent is -1)
(Put 2 zeros at the bottom because exponent is -2)
(Put 3 zeros at the bottom because exponent is -3)